LITERATURE REVIEW ON APPLYING UNIVERSAL DESIGN FOR LEARNING (UDL) IN PRAGMATIC DEVELOPMENT FOR CHILDREN WITH AUTISM SPECTRUM DISORDER IN INCLUSIVE PRESCHOOLS - Thi Anh Thu, Nguyen; Thi Thao, Do; Thi Ben, Pham (HNUE Journal of Science: Journal of Educational Science, 2024)
Universal Design for Learning (UDL) is a flexible educational framework designed to meet the diverse learning needs of all children, particularly those with special needs, such as children with Autism Spectrum Disorder (ASD). This article employs a descriptive review method to analyze and synthesize educational strategies and supportive tools from 36 research studies that utilized the UDL framework to enhance pragmatic language development for children with ASD in inclusive classrooms. It highlights the role of UDL in improving communication and social interaction through teaching strategies and tools while emphasizing the importance of integrating theoretical and practical elements in applying UDL to both inclusive classrooms and special education programs. The article concludes with recommendations for applying UDL to foster pragmatic language development for children with ASD in inclusive preschools in Vietnam, aiming to create an optimal and supportive learning environment.